DUKUNGAN FILIPINA TERHADAP AUKUS 2021-2023 - Firsa, Kheista Mardhatillah; Yuniati, Sri; Molasy, Honest Dody (Khazanah: Jurnal Mahasiswa, 2024)
The establishment of AUKUS as a response to China's aggressive movement in claiming the South China Sea has become a debate in the region because it allegedly violates ASEAN's non-nuclear principle, SEANWFZ. ASEAN member states tend to object and concern about nuclear arms competition in the region. Especially with the nuclear propulsion agreement in the development by AUKUS. Contrast to other ASEAN members, the Philippines openly supports AUKUS, as proven by the release of an official statement by the Philippine Minister of Foreign Affairs shortly after the establishment of AUKUS. In the statement, the Philippines stated that the country would fully support the AUKUS in the region and also denied allegations that the AUKUS violated the SEANWFZ. Using neorealism theory and the concept of bandwagoning, its known that the Philippines has its own reasons. The results of this study show that the Philippines' support for AUKUS is the Philippines response to the threat of China in the South China Sea. China's claims overlapping with the Philippines' EEZ caused the Philippines to feel threatened. The Philippines believes that AUKUS can reduce China's movements in the South China Sea and maintain the security stability of the Indo-Pacific region from China's threats. In addition, the Philippines argues that ASEAN doesn’t have sufficient military capabilities in dealing with China's so that an equal balance is needed in this case is AUKUS. With the Philippines supporting AUKUS, the Philippines can also strengthen relations with the United States, Australia and the United Kingdom.